ANALISIS PEMBENTUKAN KARAKTER INTEGRITAS SISWA MELALUI PEMBELAJARAN PPKN DI SMP N 3 KOTA JAMBI - Eva Gustiani; Alif Aditya Candra; Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue currently faced at SMP N 3 Kota Jambi is the low level of student integrity. This is evident from frequent violations such as tardiness, truancy, and disobedience to school rules. These behaviors indicate that efforts to strengthen students' integrity have not been fully implemented. This research aims to understand how integrity character is developed through Civics Education (PPKn) at SMP N 3 Kota Jambi, as well as to identify the supporting and inhibiting factors involved. The study was conducted using a descriptive qualitative method, with data collected through in-depth interviews, participatory observation, and documentation. The results show that the development of integrity character through PPKn learning is progressing, although challenges remain. Values such as honesty, justice, and responsibility are being taught, but not all students consistently apply them. For example, cheating and unfair treatment among peers are still common. Teachers and school leaders serve as role models, but student consistency in adopting positive behavior needs improvement. While students’ social responsibility is fairly strong, academic responsibility remains an issue, with some students often late or failing to complete assignments. Therefore, a more consistent and collaborative effort between teachers, the school, and parents is needed so that the values of integrity are not only understood but also internalized and reflected in students' daily behavior.